Penggunan Telepon Seluler Di Kalangan Mahasiswa Fisip Universitas Riau - ", MARIYUSNI; ", Syafrizal, (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The aim of this research is to know about the use of cell phone in the society of the students in Faculty of social and politic knowledge, in the University of Riau. In this research, there are some fundamental problems : First, the function of the cell phone for the students of Faculty of social and politic knowledge in the University of Riau. Second, the way students in Faculty of social and politic knowledge allocated their fund for their cell phone. And the third, the cell phone as their life style. The technique of collecting data is using the descriptive qualitative analysis. It is an analysis which given an information about the situation, indication and phenomenon in details based on the reality that to be found.After conducting the research, the researcher analyzed that most of students who use the cell phone are female sex and living far from their parents, so it means that they live in the outer part of Pekanbaru city, or even outer part of Riau Province. Most of them are just busy with their lecture, and only 2 % of them are taken a part time jobwhile their doing their lecture. It is because they are in the early degree, besides that some of them thought that they just want to focus on the lecture they afraid that if they take a part time job it will disturb their study. About the fund allocation, the data shown that the respondents are usually get the money from their parents, they tend to used the money to buying pulse for communication. However, the researcher dividing the functions of the cell phone into some functions : First, the cell phone as a tool for communication. Second, the cell phone as a tool to get the information. Third, the cell phone as a tool for entertainment. Fourth, the cell phone as an internet media. Fifth, the cell phone as a tool for photography. And then the last, it is used for games.The cell phone which is a technology for communication, not only have some positive functions. But, it also have some negative sides, for example the cell phone which has some fiturs such as bluetooth and camera which can be used for watching porn movie, indeed taking a porn picture or video. Also, the use of cell phone can gives a bad effect for the users such as consumtive behaviour, if the using of the cell phone is not balance with it’s benefit. In conclution, based on 40 responsents, we know that they use the cell phone because : 1) they need a communication tool, 2) because of social environment, and 3) the need for entertainment.Keyword : cell phone, lifestyle and function cell phone.